Skin explosion of double-layer conductors in fast-rising high magnetic fields - Chaikovsky S. A.; Oreshkin V. I. Vladimir Ivanovich; Datsko I. M.; Labetskaya N. A.; Ratakhin N. A. Nikolay Aleksandrovich (2014, 2014)
Title screen